Unheard, theatrically speaking : does the integration of physical theatre and folk media in theatre for development enhance or inhibit communication in community interventions? A case study on Seka Theatre Troupe - Banda, Benne E. (My University, 2013)
This study was undertaken in Mfuwe, the South Luangwa Game Management area in the Eastern province of Zambia, to interrogate the declining integration of folk art, traditional media and visual aesthetics in Theatre for Development (TfD). SEKA Theatre Troupe was the entity under the microscope in this ethnographic research process conducted through Theatre for Development performances. The lamentable decline in the use of the abundant traditional cultural resources in the TfD practice in Zambia has led to the flourishing of a loquacious top-down message delivery system in an era where the artistes are no longer an authoritarian all-knowledgeable spoon-feeding entity. The performance artiste must be a change agent who facilitates new thinking through the practice of an empowering living theatre as espoused by theatre performance gurus such as Peter Brook and Augusto Boal. The survival and prosperity of the Zambian cultural heritage is at stake in face of a western cultural onslaught proficiently facilitated through the multi-pronged approach of the international media. The artiste is the bastion of hope that buffers the intensity of such cultural onslaught. The robust cache of traditional intellect is being sidelined to the periphery of a people’s lives, in the traditional homelands where it is flaunted as tourist attractions instead of being a cherished and nurtured way of life. This study’s findings give pointers to solutions to heal the heartrending growing gap between the Zambian performing artistes, especially in TfD, and the vibrant local cultural forms of expression. It foregrounds how important it is to salvage the remaining precious gems of Zambian indigenous heritage for posterity as well as prosperity. All hope is not lost yet, as demonstrated by SEKA Theatre Troupe, which has daringly chosen to embark on the less popular Theatre for Development genre among Zambian Community /TfD practitioners. SEKA, through integration of popular arts and cultural practices has taken the rural voice of the common man in the wilderness of South Luangwa Game Management area and made it heard in the corridors of policy makers internationally; be it on the HIV and AIDS scourge or championing the restoration of the world’s ecosystems or even their mainstay – mitigating the wildlife and human conflict through theatre in Mfuwe.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, School of Arts (Dramatic Arts), 2012